Genetic diversity of pran (Allium cepa var. prolliferum) in Kashmir - K A Mir, M A Sheikh, M H Khan,, J I Mir, N Ahmed, S Wajida, R Rizwan,; U Noor, Z F Shafia, (Journal of Spices and Aromatic Crops, 2013)
Ten pran genotypes were evaluated using RAPD markers to determine the genetic relationships among genotypes showing morphological variations. Fourty three decamer primers were used in this study. Genetic diversity in the genotypes studied was analyzed using several variability parameters. Genotypes were grouped into two main clusters based on jaccard similarity coefficient. A dendrogram based on UPGMA analysis grouped the ten genotypes into two main clusters. Genotypes representing cluster-I are superior over genotypes in cluster-II with respect to yield attributes. Some genotypes did not show any similarity with either cluster, depicting their diverse nature. The grouping that was obtained with the RAPD analysis was at par with the morphological grouping based on yield attributes. The results of Principal Co-ordinate (PCO) analysis were comparable to the cluster analysis. Finally, the investigation of the genetic variation of pran with RAPD indicated that this marker is a suitable tool for assessing polymorphism and estimating the genetic similarity.